Effect of Red Fruit Oil on Ovarian Follicles Development in Rat Exposed to Cigarette Smoke - Utami, Isrotun Ngesti; Yuniwarti, Enny Yusuf; Saraswati, Tyas Rini (Biosaintifika: Journal of Biology & Biology Education, 2018)
Red fruit oil (Pandanus conoideus Lam) contains active substances in the form of alpha-tocopherol, beta-carotene and unsaturated fatty acids that can potentially be antioxidants. This study aims to examine the effect of red fruit oil (Pandanus conoideus) on the development of ovarian follicles of rat exposed to cigarette smoke, (in increasing the number of primary follicles, secondary follicles, tertiary follicles and ovarian weight). This study used Completely Randomized Design with 20 female rats (3 months old) divided into 4 treatment groups: P0 (Positive control), P1 (negative control of exposure to cigarette smoke for 8 days), P2 (exposure to cigarette smoke for 8 days + 0.1 ml red fruit oil) and P3 (exposure of cigarette smoke for 8 days + 0.2 ml red fruit oil) with 5 time repetition and 28 days red fruit treatment for the research parameters were the number of primary follicles, secondary follicles, tertiary follicles and ovarian weight. The data obtained were analyzed using one-way ANOVA with 95% confidence level (P < 0.05). The results showed that the administration of red fruit oil at doses of 0.1 ml and 0.2 ml was not significantly affecting (P > 0.05) the number of primary follicles, secondary follicles, tertiary follicles and ovarian weight, so it can be conclusion that the administration of red fruit oil at a dose of 0.1 ml and 0.2 ml cannot increase the number of primary follicles, secondary follicles, tertiary follicles and ovarian weight in rat exposed to cigarette smoke.